Historical climate‐human‐ecosystem interaction in East Africa: a review. (16th November 2012) - Gelorini, Vanessa; Verschuren, Dirk
Abstract: The palaeoecological visibility of historical human impact on natural ecosystems in tropical East Africa is strongly impeded by an overriding dominant signature of climate change at decadal‐to‐millennial time scales. Better knowledge of the relative magnitude and timing of present and past human impact and climate variability is, however, instrumental to properly assess the resilience, and recovery potential, of East Africa's natural ecosystems. Here, we briefly review comprehensive previous attempts to assess past ecosystem responses to climate change and human impact. We further discuss some key issues of climate‐human‐ecosystem relationships in a multidisciplinary framework and address some future challenges and outcomes, which may pave the way to a better understanding of past climate‐human‐ecosystem interaction‐ in tropical Africa.